Macroeconomic variables and stock market performance empirical evidence from sri lanka - Kengatharan, L.; Jeyan Suganya, D.F. (University of Jaffna, 2021)
The study aims is to examine the impact of selected macroeconomic variables on stock market performance. The current study uses annual data from the Central Bank of Sri Lanka to look at the effect of macroeconomic variables on stock market performance in Sri Lanka from 1990 for a 30 years period. The stock market performance is measured using the All Share Price Index (ASPI), and macroeconomic variables such as interest rate, inflation, real exchange rate and money supply have been selected to conduct the study. The data was analyzed using the Auto Regressive Distributed Lag (ARDL) bounds test after all variables were converted to log form. The Augmented Dickey-Fuller (ADF) test was used to ensure that the data was stationary. Breusch-Godfrey LM Test was used to detect serial correlations between variables, but no serial correlations were found in this analysis. As per the results of the ARDL test, interest rate and inflation had a negative effect on stock market performance, although exchange rate and money supply had no significant impact on stock market performance in the long run. In the short run, however, interest rates had a negative and significant impact on stock market performance, despite the fact that all other variables had no significant effect on stock market performance in short run.
Keywords: Macroeconomic variables; All share price index; ARDL test; Sri lankan stock market